An autocatalytic chromogenic and fluorogenic photochemical reaction controlled by nucleic acids - Dutta, Subrata; Mokhir, Andriy (Chemical communications, 2011)
The autocatalytic photochemical reaction, which is potentially controlled by any selected nucleic acid, is highly sequence specific and not inhibited by its products, was developed. This reaction generates colored and fluorescent products, which can be monitored by the naked eye.